Sensory-based transmethodology in practice research - Nielsen, Anne Maj (Outlines. Critical Practice Studies, 2023)
In this article, I present a sensory-based transmethodological research approach based on body-phenomenological conceptualizations of embodied memory and lived experiences, and on cultural-historical conceptualizations of modes of socializing behavior and mediating means as the nexus for personal learning and development. The transmethodology combines sensory methods to study individual research participants’ lived experiences and describe them in detail, and methods to study how these same individuals use sociocultural mediating means in communication and to make meaning of their lived experiences as participants in social communities of practice. The particular methodology was developed during practice research, where we as a research team engaged in embodied and contemplative practices together with student teachers in Denmark to explore how they experienced the effects of contemplative practices on their encounters with students, colleagues, or parents in challenging situations during their education and in school practice as newly educated teachers. The practices of the sensory-based transmethodology created a corpus of qualitative data with the potential to transform our ideas about relationship-building and education.